Effect of spraying with nano-potassium on the qualitative characteristics of date palm fruits (Phoenix dactylifera L.) Sayer cultivar - Khadim , Maysoon M. (Basrah Journal Of Date Palm Research, 2025)
The current study was conducted in a private orchard in Abu Al-Khaseeb district to investigate the effect of spraying with nano-potassium fertilizer on some qualitative characteristics of date palm fruit (Phoenix dactylifera L. cv. Sayer). The study involved spraying the nano-fertilizer at two concentrations (2 and 3 g L⁻¹) and a control treatment, with three replicates per treatment. The Experiment was designed as a randomized complete block design (RCBD), and the significance of differences between treatments was tested using the least significant difference (LSD) test at the 0.05 significance level. The results showed that spraying with nano-potassium fertilizer significantly affected all studied characteristics compared to the control treatment. Spraying at a concentration of 3 g L⁻¹ led to a significant increase in the percentage of soluble solids, vitamin C, and the percentage of dry matter in the fruit compared to the control treatment. The 3 g L⁻¹ concentration also showed a significant increase in the total sugar content of the fruit compared to the control treatment. A concentration of 3 g L⁻¹ resulted in a significant decrease in fruit moisture content compared to the control treatment.